Textile-based triboelectric nanogenerators via electroless plating for fabricating electrode material: Study of the relationship between electrostatic-charge density and strain in dielectric material. (8th February 2022) - Gui, Chengmei; Zhang, Ruxia; Chen, Zhenming; Wu, Wangping; Li, Honglin; Huang, Junjun
Abstract: Textile-based cotton was developed to fabricate the support for triboelectric nanogenerators (TENGs), which would facilitate the improvement of the device wearability and comfort. But, it is difficult to achieve the fabrication of metal textile-based cotton for electrode materials using traditional technology. In this regard, a textile-based TENGs via electroless plating on cotton surface for fabricating electrode material was established, the output performances under different external forces were studied comprehensively to obtain a full understanding of the relationship between the density of electrostatic charge (δ) and strain of polydimethylsiloxane (PDMS) dielectric material. Results showed that active groups on the rough cotton surface would facilitate the adsorption of Pd 2+, and then reduce of Ni 2+ to Ni atom in electroless nickel solution. As a result, core-sheath micronfiber yarn with weave structure was fabricated. It is flexible, lightweight, flexible with typical performance of TENGs electrode. The device had stable and excellent performances, and a maximum open-circuit voltage of about 8.3 V was observed from stress of 3.8 kPa or strain of 1.7 × 10 −6 on PDMS layer. More importantly, a new calculation method for the PDMS strain of formation δ was proposed by equation of state. It was also revealed that the δ and PDMS strain represented a linear regression relation when the device under weigh mass of 0.22–0.52 kg, stress of 0.69–1.63 kPa and strain of 0.3–0.72 × 10 −6 . Nevertheless, further increasing stress, actual δ value is firstly higher and then lower than the theoretical value due to fabric fiber deformation. Graphical abstract: Image 1